Pendekatan Futuristik - Wahyuni, Dini Sri; Yuliana, Yuliana; Ilmi, Darul (ANTHOR: Education and Learning Journal, 2023)
Every student is an idealized human resource to become a source of strategic strength for the nation now and in the future. The construction of national and state life is determined by the quality of students who are formed properly and correctlythrough a learning process. A learning concept designed for students in the future by considering the essence and main functions of education in developing the quality of human resources in the future. The concept of futuristic learning is used to prepare oneself for the future, therefore a wise attitude is needed in facing globalization, namely by preparing oneself as best as possible by taking advantage of the opportunities that are open in it. The success of students in the world of education,one of which is from the learning process that they follow. The multicultural learning process that involves the role of educators and students is indeed a learning process that involves two strategic student subjects. Educators are the ones who transform knowledge about multicultural values, while students are the ones who accept them to be used as knowledge or a foothold in building attitudes and behavior amidst diversity. This can be a capital to face the futuristic aspect